2011
DOI: 10.1134/s1021443711020233
|View full text |Cite
|
Sign up to set email alerts
|

Role of lipoxygenase and allene oxide synthase in wound-inducible defense response of pea

Abstract: Abstract-Lipoxygenase (LOX) and allene oxide synthase (AOS) are key enzymes in the jasmonic acid (JA) biosynthesis pathway. In this work, the role of LOX and AOS in defense response induced by wounding was investigated using pea (Pisum sativum L., cv. Ning Xia) seedlings as the material. The results showed that wound induced "JA burst" was accompanied by the activation of LOX and AOS and the accumulation of their mRNAs; applied JA also stimulated the accumulation of LOX and AOS. Further experiments conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…; Yang et al . ), however, the involvement of PAL in lignin synthesis and lodging resistance has not so far been explored in any detail. Thus, it might not be accidental that PAL becomes a causal link between wounding and lignin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…; Yang et al . ), however, the involvement of PAL in lignin synthesis and lodging resistance has not so far been explored in any detail. Thus, it might not be accidental that PAL becomes a causal link between wounding and lignin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous JA stimulated transcription of the AOS gene in rice during the development of resistance to Magnaporthe grisea (Mei et al, 2006). JA content in potato plants correlated with transcriptional activity of the AOS gene, and enzymatic activity of AOS (Yang et al, 2011). Potato plants have an OPR gene encoding the peroxisomal polypeptide 43.9 kDa and pI c. 7.72, which showed maximal levels at 2 h post-wounding (D ıaz et al, 2012), whereas the maximal transcript levels of the AOS gene was observed at 4 h hours post-wounding (Mei et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Exogenous JA stimulated transcription of the AOS gene in rice during the development of resistance to Magnaporthe grisea (Mei et al ., ). JA content in potato plants correlated with transcriptional activity of the AOS gene, and enzymatic activity of AOS (Yang et al ., ). Potato plants have an OPR gene encoding the peroxisomal polypeptide 43.9 kDa and pI c .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This signaling molecule led to an increase in LOX activity as well as endogenous JA content (Figure 1). Time course experiments (Figure 2) showed that the LOX activity was clearly detectable in the wheat callus after 6 h exposed to MeJA and increased continuously for the next 18 h. Furthermore, SHAM, which is an efficient inhibitor of JA biosynthesis, could suppress LOX activity and gene expression (Kn fel et al, ӧ 1984;Gao et al, 2003;Yang et al, 2011). It was reported that SHAM inhibit LOX activity by 90% and prevent the synthesis of the vegetative storage protein mRNA (Macrì et al, 1994;Staswick et al, 1991).…”
Section: Discussionmentioning
confidence: 99%